Croton (Euphorbiaceae) of the Brazilian state of Paraná: an annotated checklist, species distribution, and identification key - Pereira, Amanda Da Paixão Noronha; Riina, Ricarda; Caruzo, Maria Beatriz Rossi (Phytotaxa, 2022)
Croton is a megadiverse pantropical genus with about 1200 species. The genus can be easily recognized by a set of characters that include indumentum of stellate or lepidote trichomes, colored or clear latex, leaves often with nectary glands, and terminal inflorescences. We focus on the State of Paraná in southern Brazil, where we identified a gap in knowledge of Croton. This study was based on fieldwork and herbarium surveys that allowed us to document all Croton species occurring in the state. We recognize 41 species for the state and provide an identification key, taxonomic notes, and distribution maps for all species. We also include photographs and carry out lectotypifications when necessary. We expect this work will contribute to a better understanding of Croton diversity and distribution in southern Brazil.